Protective effects of coumestrol on lipopolysaccharide-induced acute lung injury via the inhibition of proinflammatory mediators and NF-κB activation. (July 2017) - Yuk, Heung Joo; Lee, Jae Won; Park, Hyun Ah; Kwon, Ok-Kyoung; Seo, Kyeong-Hwa; Ahn, Kyung-Seop; Oh, Sei-Ryang; Ryu, Hyung Won
Highlights: Coumestrol attenuates the influx of inflammatory cells into the lung of ALI mice. Coumestrol inhibits the production of inflammatory mediators. Coumestrol suppresses the activation of NF-κB and the reduced expression of SOD3. Coumestrol has an anti-inflammatory activities in LPS-stimulated RAW264.7 macrophages. Coumestrol can develop as a therapeutic agent against ALI. Abstract: Few studies have reported on the antioxidant and anti-inflammatory properties of coumestrol (CM). In this study, CM not only significantly attenuated inflammation in acute lung injury (ALI) mice but also reduced the production of nitric oxide (NO), tumour necrosis factor-α (TNF-α) and interleukin-6 (IL-6) and suppressed nuclear factor-kappaB (NF-κB) activation in lipopolysaccharide (LPS)-induced RAW264.7 macrophages. Interestingly, treatment with CM significantly attenuated the infiltration of inflammatory cells into the lung. CM decreased the levels of pro-inflammatory molecules, such as reactive oxygen species (ROS), TNF-α and IL-6, in the bronchoalveolar lavage fluid (BALF) of ALI mice. CM also inhibited the release of NO in the serum and reduced the expression of monocyte chemoattractant protein-1 (MCP-1) in the lung. In addition, CM suppressed the activation of NF-κB and the reduced expression of superoxide dismutase 3 (SOD3) in the lung. Our findings suggest that CM possesses protective effects in an ALI animal model.